(3QSGdI aj QaY GdGTJHGg Yf YdejI GSe Gddgs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g`s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Edi ehdGg GdNHjQ YHO GdZfj Hf GdfGHdSj GdMfaj YGedg Gddg JYGdi HdWag GdNaj(B: (3bO SCdfj HYV GdCUMGH Cf CcJH TjFG Ydi JYQja UhQI Gdbde hGdLhGHs
(3BNQgG (B:s
(3aBOe Ydjg GdSdGe MjfFP eNdhb Ydi UhQI LejY GdYGde hUhQI LejY GdYGde eaYdI Ydi UhQI GdCaYGd GdEdgjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs